Reply to the 'Comment on "Migration-assisted, moisture gradient process for ultrafast, continuous CO2 capture from dilute sources at ambient conditions"' by J. Casado, Energy Environ. Sci., 2022, 10.1039/D2EE00555G. Issue 9 (8th August 2022) - Sartape, Rohan; Prajapati, Aditya; Kani, Nishithan C.; Rojas, Tomás; Dandu, Naveen K.; Dhakal, Pratik; Thorat, Amey S.; Xie, Jiahan; Bessa, Ivan; Galante, Miguel T.; Andrade, Marcio H. S.; Somich, Robert T.; et al.
Abstract : Prajapati et al. developed a novel, robust, modular and industrially-scalable CO2 capture process that utilizes a migration-assisted moisture gradient (MAMG) process.